A Novel True Triaxial Apparatus for Testing Shear Seepage in Gas-Solid Coupling Coal - Gang Wang; Pengfei Wang; Yangyang Guo; Wenxin Li (Geofluids)
To study the effects of shear stress on the mechanical and seepage properties of gas-bearing coal in three-dimensional stress conditions, a novel true triaxial apparatus (TTA) was developed for the rigid loading of the major principal stress σ1 and the intermediate principal stress σ2, and for the flexible loading of the minor principal stress σ3. Both the upper and lateral pressure heads do not interfere with each other when loading σ1 and σ2. The control and measurement of gas flow sealed effectively in coal samples were achieved by using a gas seepage system. The TTA was used to perform a series of experiments on shear seepage in coal samples under true triaxial stress conditions. The experimental results about coal’s shear failure modes, shear stress-shear displacement curve, and permeability-shear displacement curve all showed that the TTA with its better accuracy and reliability had advantages in studying the effects of both the intermediate principal stress and shear deformation on the mechanical properties of coal samples and on the characteristics of gas seepage. Thus, it could provide a new test means for further studies on shear-induced seepage in the gas-solid coupling coal.